From the collection, ‘This House’, This Pink Suitcase by Owam Heyana - Heyana, Owam (Open Mic: A Creative Writing Journal, 2024)
Stanza Introduction: This pink suitcasewith wheels that wiggle in different directionsand is as big as if it could fit the world in itwas bought for my travels.